Language Noise Effects on Working Memory in University Students: A Between-Subjects Experimental Study - Agus Jatnika; Nadhiza Ghassani; Maritza Ramadhanti; Niar Larasati; Sabrina Katon (Penerbit Goodwood, 2025)
Purpose: This study examined whether exposure to 70 dB language noise significantly affects working memory performance among undergraduate psychology students at Universitas Padjadjaran. Research Methodology: A between-subjects experimental design was employed involving 46 psychology students selected through stratified random sampling based on SNBT 2023 scores. Participants were randomly assigned to a control group (n = 23) or an experimental group exposed to 70 dB language noise (n = 23). Working memory was measured using the Digit Span Forward Task administered via PsyToolkit. Data were analyzed using the Mann Whitney U test.Results: The control group achieved a higher mean digit span score (M = 6.70, SD = 1.22) than the experimental group (M = 6.09, SD = 1.41). However, the difference was not statistically significant (U = 200.000, z = ?1.455, p = .073), with a small effect size (r = 0.214).Conclusions: Exposure to 70 dB language noise did not significantly impair working memory performance. Nevertheless, the lower mean score in the experimental group suggests a potential negative effect that may be influenced by individual differences.Limitations: The small sample size, online experimental setting, and lack of noise sensitivity measurement may have reduced the ability to detect significant effects.Contributions: This study extends noise-cognition research in the Indonesian university context and highlights the importance of incorporating noise sensitivity measures and stronger experimental controls in future studies.